Hubungan Pengetahuan Tentang HIV/AIDS dengan Stigma Orang dengan HIV/AIDS di Kalangan Pelajar SMA - Ossie Sosodoro, Ova Emilia, Budi Wahyuni (Berita Kedokteran Masyarakat (BKM), 2009)
Background: Stigma of people living with HIV/AIDS is an aspect which disrupts the program of HIV/AIDS infection prevention. Some studies show that the widespread of stigma of people living with HIV/AIDS is related to knowledge about methods of HIV/AIDS infection. One most effective method to improve knowledge about HIV/ AIDS is education at schools. This study is carried out at Surakarta Municipality whereby knowledge about HIV/ AIDS and the presence of stigma of people living with AIDS among school age teenagers have never beenobserved.Objective: To identify the relationship between knowledge about HIV/AIDS and stigma of people living with HIV/ AIDS among senior high school students at Surakarta Municipality.Method: The study was qualitative observational with cross sectional design to get deeper explanation and offer input for policy making in introducing relevant intervention. Subject of the study were as many as 558 students of 4 junior high schools of Surakarta Municipality. Quantitative data analysis used univariable, bivariable with chi square test and multivariable with logistic regression and stratification.Result: The result of test on knowledge about HIV/AIDS showed that mean was 15.40 from maximum score of 20, whereas the result of test on stigma of people living HIV/AIDS showed that mean was 15.70 from maximum score of 21. The result of qualitative study showed that there was misunderstanding about methods of HIV/AIDS infection and the presence of stigma of people living with HIV/AIDS, either among the students or teachers. The result of bivariable analysis showed that the stigma was 3.37 times stronger among students with limited knowledge about HIV/AIDS than among those with good knowledge about HIV/AIDS.Conclusion: Students with limited knowledge about HIV/AIDS had higher risk for stigma of people living with HIV/AIDS that those with good knowledge.Keywords: stigma, HIV/AIDS